PERSPEKTIF CALON PENDIDIK TERHADAP FILOSOFIS EKSISTENSIALISME - Turmudi; Pieter Zakarias Tupamahu; Nelma Dortje Lethulur (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
This study aims to analyze prospective educators' views on philosophical existentialism in the context of education. Existentialism as a school of philosophy that emphasizes individual existence and freedom of choice is important to be understood by pre-service teachers’ in shaping a more humanist approach to learning. This research uses a descriptive qualitative approach with a literature study method supported by data collection through questionnaires to 50 pre-service teachers’. The results obtained reveal significant potential in the development of existentialism-based education through the perspective of prospective educators. A good understanding of the basic concepts, high readiness for implementation, and appreciation of existential values provide a strong foundation for a more humanist and meaningful educational transformation.